Om saam te weet en dan te luister: Edward Schillebeeckx se begrip Deus Humanissimus as die kerk se gewete - Van Wyk, Tanya ca. 20./21. Jh. (HTS teologiese studies, 2013)
To know communally first and then to listen: Edward Schillebeeckx’s notion Deus Humanissimus as the conscience of the church. In this article the notion of the conscience of the church is investigated. By deconstructing the apostle Paul’s notion of conscience and then exploring the connection he makes between knowledge and conscience, the role of critical voices of theologians within the church is examined, with special reference to the life and theology of Edward Schillebeeckx. His notion of Deus Humanissimus – the human face of God that becomes visible in Jesus Christ – is explored as the conscience of the church, with special reference to the inclusivity of the church. The Netherdutch Reformed Church of Africa (NRCA) is then described as an example of a church where knowledge and conscience presently do not correlate, resulting in the persistence of the NRCA’s self-description as an ethnic ‘people’s’ church, as it struggles on its journey to inclusivity. It is suggested that Schillebeeckx’s notion of Deus Humanissimus as the conscience of the NRCA can help this church to write a new narrative.